(3TQM GdTQGFYs - (3GdYGedj GdLHYj, GdTgjO GdKGfj, Rjf GdOjf Hf Ydj Hf CMeO, J(B966(3g`s ((3eMeO Hf Ydj Hf Ydj GdLHjdj GdYGedjs)
(3ChdgG (B:s
(3cJGH Gdhba hGdUObGJ bhdg Gdhba YbO KeQJg JMHjS GdCUd(B...s
(3BNQgG (B:s
...(3hdh cGfJ YOI GdWdGb HGFfI aGdcdGe aj LhGR JRhjLgG aj GdYOI cGdbhd aj LhGR GdQLhY(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B3(3,U(B64s
(3GdPQjYI(B:(3L(B20(3,U(B246(3,Qbe(B3516s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis